Decreased Prevalence of Autoimmune Connective Tissue Diseases in Type 1 and Type 2 Diabetes (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF To see the formatted meeting abstract.
Keywords: Rheumatology; Research